THE MAIN DIRECTIONS OF DEVELOPMENT OF THE INTERNATIONAL FINANCIAL SYSTEM IN THE CONTEXT OF GLOBALIZATION - Nabiddin Mannonov; Mavlonov Sunnatbek (Scholar Express Journals, 2022)
This article provides comprehensive research on the process of financial globalization, the international financial system, global financial formation, the important role of financial security in achieving the stability of the global financial architecture, the role of transnational corporations (TNCs) in the development of capital movements in international finance. and conclusions are given Introduction.
Keywords: Financial globalization; international financial system; financial security; financial architecture